Pituitary-Directed Therapies for Cushing’s Disease - Langlois, Fabienne; Chu, Jennifer; Fleseriu, Maria (Frontiers in Endocrinology, 2018)
Cushing’s disease (CD) is caused by a pituitary corticotroph neuroendocrine tumor inducing uncontrolled hypercortisolism. Transsphenoidal surgery is the first-line treatment in most cases. Nonetheless, some patients will not achieve cure even in expert hands, others may not be surgical candidates and a significant percentage will experience recurrence. Many patients will thus require medical therapy to achieve disease control. Pharmacologic options to treat CD have increased in recent years, with an explosion in knowledge related to pathophysiology at the molecular level. In this review, we focus on medications targeting specifically pituitary adrenocorticotropic hormone (ACTH)-secreting tumors. The only medication in this group approved for the treatment of CD is pasireotide, a somatostatin receptor ligand. Cabergoline and temozolomide may also be used in select cases. Previously studied and abandoned medical options are briefly discussed, and emphasis is made on upcoming medications. Mechanism of action and available data on efficacy and safety of cell cycle inhibitor roscovitine, epidermal growth factor receptor (EGFR) inhibitor gefitinib, retinoic acid, and silibinin, a heat shock protein 90 (HSP90) inhibitor are also presented.